EFFECT OF BIOINOCULANTS ON GROWTH AND YIELD OF AFRICAN MARIGOLD ( AN MARIGOLD (TAGETES ERECTA L.) CV. PUSA NARANGI . PUSA NARANGI GAINDA - BHATT, DIPAL; DESA, J. R; BHAKTA, DEEPTI (The Bioscan, 2016)
To study the effect of bioinoculants on growth and yield of African marigold (Tagetes erecta L.) cv. ‘Pusa Narangi Gainda’ an experiment was carried out with sixteen treatment combinations, consisting two levels of nitrogen i.e. full N (200 kg N/ha) and 3/4thN (150 Kg/ha) and two levels of Phosphorus i.e. full P2 O5 (60 kg P2O5 /ha) and 3/4th P2O5 (45 kg P2O5/ha) with bioinoculants i.e. Azotobacter and Phosphate Solubilizing Bacteria (PSB). The results revealed that the vigorous growth in terms of plant height (167.40 cm), number of branches per plant (43.20), plant spread (N-S) (102.60 cm) and dry matter content of plant (68.40%) was noted significantly in plants treated with Azotobacter + PSB + 3/4th dose of N + full dose of P2 O5 (T15). The plant receiving same treatment recorded maximum flower diameter (6.60 cm), stalk length (24.70 cm), number and weight of petals per plant (189.90 and 2.93 g, respectively), vase life (5.40 days), maximum number of flowers/plant (42.20), weight of flowers/plant (147.50 g) and yield of flowers (137.40 q/ha). Biofertilizers along with chemical fertilizers found beneficial for vigorous growth of plant and for maximum yield of better quality flower in African marigold.